The genre of Acts and collected biography - Adams, Sean A. 1981- (Cambridge Cambridge University Press, 2013)
It is widely accepted by New Testament scholars that the Gospel of Luke and the Acts of the Apostles probably originated as two parts of one work by a single author. In spite of this, the books have been assigned to very different genres: Luke is traditionally viewed as a biography of Jesus, and Acts as a history of the early church. Comparing in detail the structure and content of Acts with the formal features of history, novel, epic and biography, Sean Adams challenges this division. Applying both ancient and modern genre theory, he argues that the best genre parallel for the Acts of the Apostles is in fact collected biography. Offering a nuanced and sophisticated understanding of genre theory, along with an insightful argument regarding the composition and purpose of Acts, this book will be of interest to those studying the New Testament, Acts, genre theory and ancient literature.
Introduction -- Modern and ancient genre theory -- Ancient individual and collected biographies -- Acts as collected biography -- Characterisation in Acts -- Peter, Paul and the ending of Acts -- Conclusion -- Appendix 1. Literary topoi in ancient Greek biographies -- Appendix 2. References to biographical works in Diogenes Laertius' The Lives of the Philosophers -- Appendix 3. Divisions in collected biographies
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Bible -- Criticism, interpretation, etc; Biography as a literary form; Literary Form; Bible ; Acts ; Criticism, interpretation, etc; Literary Form; Biography as a literary form